The Relationship Between Organizational Climate and Quality of Work Lifeof Furniture Company Employees in Nonthaburi Province (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to 1) study the organizational climate of furniture company employees in Nonthaburi Province, 2) study the quality of working life of furniture company employees in Nonthaburi Province, and 3) study the relationship between organizational climate and quality of working life of furniture company employees in Nonthaburi Province. The sample consists of 400 furniture company employees using convenience sampling method, only those who are furniture company employees in Nonthaburi Province. The research instrument is a questionnaire. Data analysis uses statistics such as frequency, percentage, mean, standard deviation, and Pearson’s product moment correlation coefficient. The research results found that 1) The overall level of opinions on the organizational atmosphere of furniture company employees in Nonthaburi Province had the highest average value. When considering each aspect, it was found that the support aspect had the highest average value. 2) The overall level of opinions on the quality of working life of furniture company employees in Nonthaburi Province had the highest average value. When considering each aspect, it was found that all aspects were at a high level. The ranking from highest to lowest average value was as follows: social relations, management style, social relations, development of worker potential, safe working conditions that are not harmful to health, freedom from work, advancement, and fair and adequate compensation, respectively. 3) The relationship between organizational atmosphere and quality of working life of furniture company employees in Nonthaburi Province was very high, with statistical significance at the 0.01 level.